Parents' Recognition of Their Children's Attachment Object - OTAKI Midori; NAKATUKO Ayako (Journal of Home Economics of Japan, 1994)
There were 2 purposes for this study. One of them was to find out the difference between the fathers' recognition of their children's attachment object and the mother's, and the other was to study the factors which influence the parents' recognition of their children's attachment object. The subjects were 665 pairs of parents who had a child or children going to nursery schools. The survey was carried out in 14 different everyday situations. The results were as follows : 1) Both the fathers and the mothers think that their children consider the mothers more largely as attachment objects than the fathers.2) The fathers think that they are more important for their children as the attachment objects than the mothers think the fathers are, and vice versa.3) It was found that their children's genders and ages as well as their wives' occupations have a very strong influence over the fathers' recognition.4) It was found that their children's ages and their own occupations have a great influence over the mothers' recognition while their children's genders and mother-child contact time have a moderate influence. 子どもの愛着対象に関する父親と母親の認知における実態と父親と母親の認知に影響する要因を明らかにするために本研究を行った.対象は, 保育園児をもつ665組の父親と母親である.彼等を対象に14の異なる生活場面において, 子どもが誰を愛着対象としているかについて調査し, 以下の結果を得た.1) 父親も母親も, 子どもは母親を最も多く愛着対象にしていると認知している.2) 父親も母親も子どもとの情愛的関係において, パートナーが考えるよりも自分は子どもから重要な存在であると思われていると考える傾向がある.3) 父親の認知には, 子どもの性や年齢と妻の就業形態が大きな影響を与えていることが明らかになる.4) 母親の認知には, 子どもの年齢と母親の就業形態が大きな影響を与え, また, 子どもの性と母親と子どもの接触量もかなりの影響を与える原因であることが明らかになる.